THE MAIN METHODOLOGICAL APPROACHES OF TEACHING THE ANATOMY TO STUDENTS OF THE FACULTY OF FOREIGN CITIZENS AT HIGHER MEDICAL SCHOOLS - Knyazevych-Chorna, T.V. (World of Medicine and Biology, 2012)
This work presents the mail methodological approaches and guidelines to the teaching of anatomy with aim to optimize the learning process and acquire the knowledge by the students of the Faculty of foreign citizens at higher medical schools.